Business Intelligence Challenges for Independent Game Publishing. (21st January 2020) - Su, Yanhui; Backlund, Per; Engström, Henrik
Abstract : With the continuous development of the game industry, research in the game field is also deepening. Many interdisciplinary areas of knowledge and theory have been used to promote the development of the game industry. Business intelligence technologies have been applied to game development for game design and game optimization. However, few systematic research efforts have focused on the field of game publishing, particularly with regard to independent (indie) game publishing. In this paper, we analyse data collected from a set of interviews with small indie game developers. The results indicate that most of the indie game developers have already used business intelligence for game self-publishing, although three main challenges have been identified: first, how to conduct marketing promotion and improve the return on investment (ROI); second, how to collect game publishing data; and third, how to analyse the data in order to guide game self-publishing. Our interviews also reveal that the business model applied to a game significantly impacts the role of game analytics. The study expands and advances the research on how game analytics can be used for game publishing, particularly for indie game self-publishing.